Towards an oscillation-free, mass conservative, Eulerian-Lagrangian transport model - Oliveira, A. (2010)
Ten numerical schemes to reduce spurious oscillations in transport simulations were implemented and tested in an Eulerian-Lagrangian control volume finite element model. The schemes included both new and existing Flux Corrected Transport (FCT) algorithms and non-linear filters. The ability of the methods to eliminate numerical oscillations while preserving mass and minimizing the introduction of numerical diffusion was compared in 2D tests of varying complexity. The application of local mass correction algorithms was shown to be vital to avoid the introduction of mass errors by FCT. While none of the methods emerged as optimal for all cases, a new FCT method with a local mass correction scheme and a non-linear filter can be recommended as the best approaches in general. The method of choice depends on the problem being solved, in particular on the concentration gradients and on the grid resolution.